Deep learning essentials : your hands-on guide to the fundamentals of deep learning and neural network modeling /: your hands-on guide to the fundamentals of deep learning and neural network modeling. (2018) - Di, Wei; Bhardwaj, Anurag; Wei, Jianing
No abstract available